Soft Contact Lenses as a Good Option for Adolescent with Anisometropia: Poster Presentation - Case Report - Resident - Widya Wira Putri; dr. Ani Ismail, SpM(K); dr. Eva Kumalasari, SpM (Majalah Oftalmologi Indonesia, 2023)
Introduction : Anisometropia is a condition of asymmetric refraction between the two eyes. Adequate anisometropia treatment, such as SCL (Soft Contact Lens) is required to provide binocular vision, patient comfort and also adolescent’s appearance. Case Illustration : A 16 years old woman came to the RS Khusus Mata Sumatera Selatan. She complained of blurred vision since 6 years ago, and not feeling comfortable using spectacle. The ophthalmologic examination revealed that uncorrected visual acuity was 2/60 ph 6/12 for right eye and on left eye is 6/30 ph 6/7.5. Best corrected visual acuity was 6/6 using S-7.00 on the right eye and left eye was 6/6 using correction S-3.00 but she was not comfortable. The base-curve measurement of the SCL was 8.60 mm for the both eyes and the diameter was 14.2 mm. After the contact lenses attached , obtained that S-7.00 D for the right eye and S-3.00 for the left eye could reach 6/6 in both eyes, she was more comfortable wearing SCL than spectacle. Discussion : Anisometropia can cause aniseikonia which is characterized by differences in the size of the image in the two eyes. One way to reduce aniseikonia by reducing the vertex distance, soft contact lenses canbe a choices to maintain binocular vision and minimalized the aniseikonia. Contact lenses significantly improved Adolescent’s appearance and activities, which lead to an overall improvementin satisfaction with vision correction, compared using spectacle. Conclusion : SCL is one of a good option for Adolescent with anisometropia that can provide good visual acuity, and also adolescent’s appearance.